(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The key focus of the presented research is on sustainable thermal insulation biocomposites which can be made from locally available hemp and lime. The main gains of the use of such material are given, with emphasis on CO2 reduction. In the first stage samples of an artificial hydraulic lime using three different limes and three hydraulic additives are created and tested, the one with the highest compressive strength (DL60 lime with 40% metakaolin addition) are chosen for further research. In the second stage three different density mixes with the chosen binder are created, optimal hemp/binder ratio is determined, as well as compressive strength and thermal conductivity. Results indicate that created mixtures have good potential as self-bearing thermal insulation material used in low-rise buildings.